Exploration of Green Library Concept with Artificial Intelligence - Eni Amaliah; Febrian, Muhamad Khadavi; Saputra, Julian Hadi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
The rise of green libraries signifies an increasing commitment to sustainability within library operations. These initiatives seek to reduce environmental impact through decreased paper consumption, efficient energy use, and environmentally responsible management practices. Simultaneously, the integration of Artificial Intelligence (AI) presents new opportunities to enhance operational efficiency and the quality of library services. This study investigates the intersection of green library practices and AI adoption through a descriptive qualitative literature review. The findings indicate that AI technologies, such as Natural Language Processing (NLP), chatbots, and automated systems can streamline cataloging processes, enhance information retrieval, and lessen dependence on physical resources. AI also contributes to energy efficiency through smart building management systems that automate lighting, heating, ventilation, and air conditioning (HVAC), thereby reducing overall carbon emissions. Furthermore, AI-assisted services expand social inclusivity by improving accessibility for users with disabilities and supporting remote and underserved communities. The bibliometric mapping analysis reveals a growing scholarly interest in sustainable innovation within library services. The study concludes that the synergy between green library initiatives and AI integration not only advances progress toward the Sustainable Development Goals (SDGs) but also positions libraries as proactive agents of environmental and social transformation. This research contributes to ongoing discussions on sustainable digital transformation in the library sector.